2011
DOI: 10.1002/chem.201002235
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Counterion on the Synthesis of ZnO Mesocrystals under Solvothermal Conditions

Abstract: Polymers and coordinating solvents have been shown to serve as templating agents to assist the precipitation of ZnO nanoparticles and address their morphology. In this work we show for the first time that a difference in the coordination strength between the polymer (poly-N-vinylpyrrolidone (PVP)) and the two Zn(II) precursor salts (nitrate and acetate) is able to promote or suppress the formation of mesocrystalline structures and even more importantly to tune their three-dimensional organization. On the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 70 publications
1
43
0
Order By: Relevance
“…This definition has been developed in recent years, where MCs are defined entirely according to their structures rather than their formation mechanism. 12 In this decade, a variety of MCs of metal oxides (for example, TiO 2 , [13][14][15][16][17][18][19][20][21][22][23] ZnO, [24][25][26][27][28][29][30][31][32][33][34] hematite (a-Fe 2 O 3 ), [35][36][37][38][39][40] maghemite (g-Fe 2 O 3 ), 41 Co 3 O 4 , 42 SnO, [43][44][45] Ag 2 O, 46 CuO [47][48][49] ), metal chalcogenides (for example, ZnS, 50,51 PbS, 52 PbSe 53,54 ), metals (for example, Au, 55 Ag, 56,57 Cu, 58 Pt, 59,60 Pd 61 ), organic compounds (for example, DL-alanine, 62,63…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition has been developed in recent years, where MCs are defined entirely according to their structures rather than their formation mechanism. 12 In this decade, a variety of MCs of metal oxides (for example, TiO 2 , [13][14][15][16][17][18][19][20][21][22][23] ZnO, [24][25][26][27][28][29][30][31][32][33][34] hematite (a-Fe 2 O 3 ), [35][36][37][38][39][40] maghemite (g-Fe 2 O 3 ), 41 Co 3 O 4 , 42 SnO, [43][44][45] Ag 2 O, 46 CuO [47][48][49] ), metal chalcogenides (for example, ZnS, 50,51 PbS, 52 PbSe 53,54 ), metals (for example, Au, 55 Ag, 56,57 Cu, 58 Pt, 59,60 Pd 61 ), organic compounds (for example, DL-alanine, 62,63…”
Section: Introductionmentioning
confidence: 99%
“…This definition has been developed in recent years, where MCs are defined entirely according to their structures rather than their formation mechanism. 12 In this decade, a variety of MCs of metal oxides (for example, TiO 2 , 13-23 ZnO, [24][25][26][27][28][29][30][31][32][33][34] Among metal oxides, TiO 2 is used in many applications that deal with environmental and energy problems (for example, photodegradation of pollutants, 67 water splitting for H 2 evolution, 68 dyesensitized solar cells 68 and lithium-ion batteries 69 ) owing to its …”
mentioning
confidence: 99%
“…For example secondary particles 160 nm in diameter composed of 5 nm primary crystallites was formed from zinc nitrate, but by using zinc acetate, a mixture of 15 nm equiaxed and elongated 40 nm by 15 nm particles was obtained. 24 It was suggested that the differences were related to the chelating effects of the acetate group in hindering the interaction of a polyvinyl butyrate additive with zinc ions during the growth phase. 24 It has been reported that changes to the ratio of OH -to Zn 2+ have only a minor effect on the size of ZnO nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO can also be grown in mesocrystalline form, as it is demonstrated in [7]. Mesocrystalline ZnO particles can be synthesized from a zinc precursor salt dissolved in dimethylformamide (DMF) with addition of polyvinylpyrrolidone (PVP) under vigorous stirring.…”
Section: Materials Optical Propertiesmentioning
confidence: 99%
“…To keep the interaction low, the inter element distances are made relatively large, which in return leads to relatively low volume fraction of the meta-atoms in conventional metamaterials. In mesocrystals, to the contrary, the material volume fraction can reach the values close to the 70% [7,8]. The standard effective medium theories like averaging, Maxwell-Garnet [9] or Bruggeman [10] approximations are believed to adequately describe particulate systems with low particle volume fractions [11].…”
Section: Introductionmentioning
confidence: 99%